Is polypharmacy beneficial or detrimental for older adults with cardiometabolic multimorbidity? Pooled analysis of studies from Hong Kong and Europe. (29th June 2020) - Cheung, Johnny T K; Yu, Ruby; Woo, Jean
Abstract: Background: Physicians often prescribe high numbers of medications for managing multiple cardiometabolic diseases. It is questionable whether polypharmacy (concurrent use of five or more medications) is beneficial or detrimental for older adults with cardiometabolic multimorbidity (co-occurrence of two or more diseases). Objective: To examine combined effects of multimorbidity and polypharmacy on hospitalization and frailty and to determine whether effect sizes of polypharmacy vary with numbers of cardiometabolic diseases Methods: We pooled longitudinal data of community-dwelling older adults in Hong Kong, Israel, and 17 European countries. They completed questionnaires for baseline assessment from 2015 to 2018 and reassessment at 1–2-year follow-up. We performed regression analyses to address the objective. Results: Among 44 818 participants (mean age: 69.6 years), 28.3% had polypharmacy and 34.8% suffered from cardiometabolic multimorbidity. Increased risks of hospitalization and worsening frailty were found in participants with 'multimorbidity alone' [adjusted odds ratio (AOR) 1.10 and 1.26] and 'polypharmacy alone' (AOR 1.57 and 1.68). With 'multimorbidity and 'polypharmacy' combined, participants were not at additive risks (AOR 1.53 and 1.47). In stratified analysis, with increasing numbers of cardiometabolic diseases, associations of polypharmacy with hospitalization and frailty were attenuated but remained statistically significant. Conclusion: Polypharmacy is less detrimental, yet still detrimental, for older adults living with cardiometabolic multimorbidity. Physicians should optimize prescription regardless of the number of diseases. Health policymakers and researchers need to consider their interrelationship in hospitalization risk predictions and in developing frailty scales.